Implementasi Metode Yanbu’a dalam Meningkatkan Kualitas Membaca Al-Qur’an Santri Putri di Pondok Pesantren Darun Najah Lumajang - khikmatul Qomariyah (Ashfiya Journal of Qualitative Insight in Islamic Studies, 2025)
This study examines the implementation of the Yanbu’a method in improving the quality of Qur’anic reading among female students at Darun Najah Islamic Boarding School, Lumajang. The study is grounded in the need for a structured and systematic approach to Qur’anic literacy, given the variability in students’ reading abilities and the limitations of traditional learning methods. Employing a qualitative phenomenological approach, this research explores the experiences and learning processes of instructors and students through in-depth interviews, participant observation, and documentation. Data were analyzed using thematic analysis to identify patterns in the implementation of the Yanbu’a method and its impact on students’ reading competencies. The findings indicate that the Yanbu’a method significantly enhances students’ Qur’anic reading skills across three key dimensions: tartīl (rhythmic and orderly recitation), faṣāḥah (articulatory accuracy), and tajwīd (rule-based recitation). The method integrates modeling, guided practice, and repetition within a structured multi-level system, enabling gradual skill development. Additionally, the effectiveness of the method is supported by factors such as disciplined learning routines, instructor competence, and a conducive pesantren environment. The study also reveals distinctive characteristics of female pesantren learning, including emotional scaffolding, consistent daily rhythms, and a supportive cultural ecology that strengthens learning outcomes. This study contributes to the development of Qur’anic pedagogy by proposing a comprehensive and context-based model of Yanbu’a implementation that integrates cognitive, psychomotor, and affective domains. It also offers practical implications for improving Qur’anic literacy programs in Islamic educational institutions, particularly in traditional female boarding school settings.